Comparing the implementation of sustainability initiatives in national and multinational fast moving consumer goods companies - Haw, Alexander Francis (My University, 2017)
In recent times increasing emphasis has been placed on the important role that corporations must play in the creation of greener economies. This has given rise to greater corporate environmental disclosure and reporting, and a wealth of research into the link between sustainability reporting and financial and environmental business performance. Notwithstanding this, it has been noted that corporate responses to environmental sustainability issues are highly variable, and very little research has been conducted to determine where businesses focus their environmental sustainability efforts and to what extent they have made measureable progress in this regard. The purpose of this study was to assess and compare the implementation of sustainability initiatives across a variety of fast moving consumer goods companies, including large multinational organisations, privately owned South African and publically traded JSE listed companies. This was achieved through the evaluation and scoring of an environmental self-assessment questionnaire distributed annually over a three year period between 2012 and 2014. In total, the survey, which covered a cross section of business relevant environmental issues, allowed for the profiling of 851 company responses. Scoring of these responses was based on a defined matrix with a grading system of 0 – 6. Results showed that overall, larger companies appear to be making significantly better progress when it comes to tackling environmental issues than their smaller privately owned competitors. Of the product categories investigated, the sustainability performance of liquor suppliers was the best while transport suppliers scored significantly lower than their peers. Publically listed JSE-listed companies and large multinational companies had similar sustainability performance to one another but both these groups performed significantly better than their privately owned South African competitors. Of those supplier Groups surveyed, JSE listed companies were the only business Group who showed significant year-on-year improvement in performance. An evaluation of scores achieved across the different environmental issues covered revealed that suppliers indicated they performed best in the areas of waste minimisation, operational energy mitigation and sustainable product design, while they made least progress when it came to climate change mitigation, sustainability reporting and biodiversity conservation. Results suggest that overall: companies made most progress on environmental issues that offered the greatest potential for increasing revenues or reducing operating costs; large public corporations performed significantly better than privately owned companies when it came to tackling environmental sustainability issues; and despite increasing emphasis being placed on transitioning to more sustainable business models, only one group of suppliers showed a measurable improvement in sustainability performance over the course of the study.
Masters in the Field of Environmental Sciences (MSc CW/RR) - GEOL7007 Research Report School of Animal Plants and Environmental Science. Johannesburg 2017.
Keywords: Corporation--Environmental aspects--South Africa; Social responsibility of business--South Africa; Economic development; Sustainability